2010
DOI: 10.1186/ar3071
|View full text |Cite
|
Sign up to set email alerts
|

Increased activity and expression of histone deacetylase 1 in relation to tumor necrosis factor-alpha in synovial tissue of rheumatoid arthritis

Abstract: IntroductionThe purpose of this study was to investigate the profile of histone deacetylase (HDAC) expression in the synovial tissue of rheumatoid arthritis (RA) compared with that of normal control and osteoarthritis (OA), and to examine whether there is a link between HDAC activity and synovial inflammation.MethodsHDAC activity and histone acetyltransferase (HAT) activity were determined in nuclear extracts of total synovial tissue surgically obtained from normal, OA and RA joints. The level of cytoplasmic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
111
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(117 citation statements)
references
References 44 publications
(49 reference statements)
5
111
0
Order By: Relevance
“…expression of HDAC 1 was correlated with expression of inflammatory cytokine TNF-α [29]. More recent studies have confirmed a role for HDAC 1 in the inflammatory tissue destruction in RA.…”
Section: Accepted Manuscriptmentioning
confidence: 71%
See 1 more Smart Citation
“…expression of HDAC 1 was correlated with expression of inflammatory cytokine TNF-α [29]. More recent studies have confirmed a role for HDAC 1 in the inflammatory tissue destruction in RA.…”
Section: Accepted Manuscriptmentioning
confidence: 71%
“…The 18 HDAC enzymes are widely expressed in tissues throughout the body and deacetylate both histone and non-histone proteins, making it challenging to determine the precise mechanism of action of different HDACi. Despite the ubiquitous nature of class I HDACs, differences in expression of these enzymes have been observed in a number of malignancies and also in rheumatoid arthritis (RA) [26][27][28][29]. This review focuses on HDACs and…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Although well proven, it is recognized that there are large individual differences in the optimal dose of MTX for RA patients (5). The reasons for those individual differences are thought to be different concentrations of intracellular MTX-polyglutamates (MTX-PGs) and different enzyme activities at MTX-active sites (6 cytokines and other mediators of inflammation, such as tumor necrosis factor-α (TNF-α) and interleukin-10 (IL-10), may also correlate with the efficacy of MTX (7,8). However, rapid clinical assays to measure these such as MTX-PGs, enzyme and cytokines are technically difficult and not available in most clinical facilities (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, only a few reports have addressed how methylation of individual CpG sites influences the promoter activity of a specific gene (6,10,11), and the relative contributions of the methylation status of each individual CpG site to the transcriptional regulation of a given gene in vivo remain largely unexplored. In addition, although epigenetic gene regulation has been broadly investigated in other contexts, little is known about the specific impact of this mechanism of gene control in musculoskeletal diseases (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%